Effect of deposition current density and annealing temperature on the microstructure and magnetic properties of nanostructured Ni-Fe-W-Cu alloys - Spasojević Milica; Marković Dušan; Spasojević Miroslav; Vuković Zoran; Maričić Aleksa; Ribić-Zelenović Lenka (Science of Sintering, 2019)
Ni-Fe-W-Cu alloy powders were obtained by electrodeposition from an ammonium citrate bath at current densities ranging between 70 and 600 mA cm-2. As the deposition current density increased, the contents of Fe and W in the alloy increased, and those of Ni and Cu decreased. The total cathodic polarization curve was recorded, and partial polarization curves for Ni, Fe and W deposition and hydrogen evolution were determined. The current efficiency of alloy deposition was measured. The powders contained an amorphous matrix and FCC nanocrystals of the solid solution of Fe, W and Cu in Ni. At high current densities, small-sized nanocrystals exhibiting high internal microstrain values were formed. Powder particles were dendrite- and cauliflower-shaped. The dendrites had a large number of secondary branches and higher-order branches containing interconnected globules. The density of branches was higher in particles formed at high current densities. The powders formed at high current densities exhibited higher magnetization. Annealing at temperatures up to 460°C resulted in structural relaxation, accompanied by an increase in magnetization. At temperatures above 460°C, amorphous matrix crystallization and FCC crystal growth took place, accompanied by a decrease in magnetization. [Project of the Serbian Ministry of Education, Science and Technological Development, Grant no. 172057]